2010
DOI: 10.2174/1874294701004010018
|View full text |Cite
|
Sign up to set email alerts
|

Callus Induction and Organogenesis in Soybean [Glycine max (L.) Merr.] cv. Pyramid from Mature Cotyledons and Embryos

Abstract: Soybean is one of the most important legumes of the world. Soybean plants are affected by several biotic and abiotic factors as well as insect pests and diseases which lower the quality and production of the crop. In order to overcome these biotic and abiotic challenges, a systematic crop improvement plan has to be followed in order to enhance crop production which involves the use of new technologies and developing new cultivars with desirable qualities. With the completion of the soybean genome sequencing pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…In our study, middle pieces of leaves (L2) showed higher callus induction capacity than basal pieces of leaves with its petioles (L1 Zebarjadi et al (2011), the highest frequency of callus formation was achieved on a medium supplemented with 0.1 mg/l 2,4-D (Das et al, 2012); 2,4-D was also effective in initiating callus in two types of explants (cotyledons and embryos) of soybean (Joyner et al, 2010). MS medium supplemented with 2,4-D (6.78 and 9.05 μm) alone and in combination with or with .26 μm) induced callus in petiole explants of Viola serpens (Vishwakarma et al, 2013).…”
Section: Discussionsupporting
confidence: 49%
“…In our study, middle pieces of leaves (L2) showed higher callus induction capacity than basal pieces of leaves with its petioles (L1 Zebarjadi et al (2011), the highest frequency of callus formation was achieved on a medium supplemented with 0.1 mg/l 2,4-D (Das et al, 2012); 2,4-D was also effective in initiating callus in two types of explants (cotyledons and embryos) of soybean (Joyner et al, 2010). MS medium supplemented with 2,4-D (6.78 and 9.05 μm) alone and in combination with or with .26 μm) induced callus in petiole explants of Viola serpens (Vishwakarma et al, 2013).…”
Section: Discussionsupporting
confidence: 49%
“…Radhakrishnan & Ranjithakumari (2007) reported that the highest cell proliferation was obtained using half seed explant of the Indian soybean cv. CO3 in presence of 13.3µM benzyl amino purine (BAP) and 13.5µM 2,4-D. Joyner et al (2010) reported that mature cotyledons of soybean cv. Pyramid produced high amounts of calli when cultured either in the media with 2,4-D or/and NAA.…”
Section: Tissue Culture Establishment Of Callus Culturesmentioning
confidence: 99%
“…(soybean), is an important seed legume from the family Fabaceae. The ability of soybean to withstand various climatic zones and environmental conditions worldwide makes it one of the most precious oil seed crops (Joyner et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Media compositions have a key role in shoot morphogenesis, the basal medium MS [37] is most commonly used for soybean organogenesis and the medium B5 [38] are useful in some approaches. Benzylaminopurine (BA) has been the most commonly used plant growth regulator either alone or in combination with a low concentration of cytokinins, kinetin or thidiazuron (TDZ) [22,39]. TDZ was reported to induce multiple bud tissue (MBT) from cotyledonary node axillary meristem which then gives shoots in the presence of BA [23].…”
Section: Organogenesismentioning
confidence: 99%